Investigating the Antimicrobial Efficacy of Liposomal Vancomycin in Gram-positive and Gram-negative bacteria- A Preliminary Mechanistic Study: Antimicrobial Effects of Liposomal Vancomycin - Serri, Azadeh; Mahboubi, Arash; Zarghi, Afshin; Moghimi, Hamid R. (Iranian Journal of Pharmaceutical Sciences, 2018)
Outer membrane of Gram-negative bacteria is a permeability barrier to many antibacterial agents, including the glycopeptide antibiotics such as vancomycin hydrochloride and as a result these antibiotics are ineffective against Gram negative bacteria. Different strategies have been described to overcome such limitation, including application of nanoparticles, as was shown in our previous studies for polymeric nanoparticles. On the other hand, some nanoparticles have the ability to reduce the permeation of drugs through biological barriers. Therefore, in this investigation, the effects of fusogenic liposomes, which are expected to interact well with biological barriers, toward antimicrobial effects of vancomycin in different bacteria, are investigated.Vancomycin-loaded liposomes were prepared by lipid film hydration method from a phospholipid mixture composed of either DPPC: DOPE: Chol or DPPC: DOPE: CHEMS, both in 1: 0.5: 1 molar ratios. Obtained liposomes were then assessed in regard to their antibacterial properties using broth microdilution method. Liposomes were prepared by lipid-film hydration followed by extrusion and probe sonication for size reduction. Encapsulation efficiency for large hydrophilic vancomycin in liposomes was found to be in the range of 0.1 to 9 % for different formulations. Probe sonicated liposomes showed smaller size and were more stable than those prepared by extrusion. Antimicrobial results showed that encapsulation of vancomycin in liposomes decreased antibacterial efficacy of vancomycin and caused MIC increments, compared to those of free vancomycin. This might indicate negligible release of this large and charged molecule from liposomes into the bacterial preplasmic space (retention of vancomycin inside liposomal cavity or lipid-drug complexation) accompanied by inability of liposomes to permeate the bacterial barrier. Further investigations are needed to explain the interaction of liposomes with bacterial membranes.